COLLATERAL DAMAGE : Britain America and Europe in the Age of Trump - Darroch, Kim (London : William Collins, 2020)
"@realDonaldTrump: The wacky ambassador that the UK foisted on the United States is not someone we are thrilled with, a very stupid guy ... We will no longer deal with him." Kim Darroch is one of the UK's most experienced and respected diplomats, and this unvarnished, behind-the-scenes account will reveal the inside story behind his resignation; describe the challenges of dealing with the Trump White House; and offer a diplomat's perspective on Brexit, and how it looked to Britain's closest ally. Darroch was the British Ambassador to the US as the age of Trump dawned and Brexit unfolded. He explains why the British embassy expected a Trump victory from as early as February 2016, what part every key figure - from Steve Bannon to Sarah Sanders - has played in Trump's administration, and what balanced policy makers on both sides of the Atlantic should consider during this era of seismic change and populist politics. A riveting account from the best-informed insider, Collateral Damage charts the strangest and most convulsive period in the recent history of Britain and the US - and shows how 30 months threatened to overturn three centuries of history....Amazon
Includes index
Keywords: Darroch, Kim; Trump, Donald, -- 1946-; Ambassadors -- Great Britain -- Biography; Biographies; Biography